Comparative Sequence and X-Inactivation Analyses of a Domain of Escape in Human Xp11.2 and the Conserved Segment in Mouse - Tsuchiya, Karen D.; Greally, John M.; Yi, Yajun; Noel, Kevin P.; Truong, Jean-Pierre; Disteche, Christine M. (Genome Research, 2004)
We have performed X-inactivation and sequence analyses on 350 kb of sequence from human Xp11.2, a region shown previously to contain a cluster of genes that escape X inactivation, and we compared this region with the region of conserved synteny in mouse. We identified several new transcripts from this region in human and in mouse, which defined the full extent of the domain escaping X inactivation in both species. In human, escape from X inactivation involves an uninterrupted 235-kb domain of multiple genes. Despite highly conserved gene content and order between the two species, Smcx is the only mouse gene from the conserved segment that escapes inactivation. As repetitive sequences are believed to facilitate spreading of X inactivation along the chromosome, we compared the repetitive sequence composition of this region between the two species. We found that long terminal repeats (LTRs) were decreased in the human domain of escape, but not in the majority of the conserved mouse region adjacent to Smcx in which genes were subject to X inactivation, suggesting that these repeats might be excluded from escape domains to prevent spreading of silencing. Our findings indicate that genomic context, as well as gene-specific regulatory elements, interact to determine expression of a gene from the inactive X-chromosome.